Idiopathic Intracranial Hypertension (IIH) Post COVID-19 Infection: Case Report - Bastola, Pradeep; Dahal, Polina; Khadka, Mandira; Gupta, Nand Kishor; Bastola, Seeksha; Koirala, Sunil (Journal of Karnali Academy of Health Sciences, 2021)
Pseudotumor cerebri or benign intracranial hypertension (BIH) or idiopathic intracranial hypertension (IIH) is a clinical condition that includes headache, papilledema, increased blood pressure, and clear cerebrospinal fluid. Multiple causes have been described for this condition, including venous sinus thrombosis, the toxicity of some substances such as vitamin A, tetracyclines and oral contraceptives, and sepsis besides patients related factors like obesity and middle-aged females. We report here a case of pseudotumor cerebri in a 28-years old lady presenting to the Department of Ophthalmology, Chitwan Medical College (CMC), Nepal with a history of COVID-19 infection two months earlier. To our knowledge, this is the first report of post-COVID-19 associated isolated Benign Intracranial Hypertension (BIH) from Nepal.